2018
DOI: 10.1021/acs.jctc.8b00294
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Pair Natural Orbitals for the Coupled Cluster Methods

Abstract: We present the coupled-cluster singles and doubles method formulated in terms of truncated pair natural orbitals (PNO) that are optimized to minimize the effect of truncation. Compared to the standard ground-state PNO coupled-cluster approaches, in which truncated PNOs derived from first-order Møller-Plesset (MP1) amplitudes are used to compress the CC wave operator, the iteratively optimized PNOs ("iPNOs") offer moderate improvement for small PNO ranks but rapidly increase their effectiveness for large PNO ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Several functional forms have been proposed including modified second-order Hylleraas-functionals [23][24][25] and other ones that utilize the overlap of the CC wave functions expanded in the full and the active virtual spaces [26,27]. The benefits of using CCSD amplitudes instead of MP1 amplitudes to define the retained virtual subspace have also been explored [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several functional forms have been proposed including modified second-order Hylleraas-functionals [23][24][25] and other ones that utilize the overlap of the CC wave functions expanded in the full and the active virtual spaces [26,27]. The benefits of using CCSD amplitudes instead of MP1 amplitudes to define the retained virtual subspace have also been explored [28].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the cost-reduction of conventional CC methods, various types of NOs are widely used to speed up local CC approaches. These include the pair natural orbitals (PNOs) [13][14][15]28] and local natural orbitals (LNOs) [48], which are pair-and orbital-specific NOs, respectively, evaluated from density matrix fragments.…”
Section: Introductionmentioning
confidence: 99%
“…414 Recently it was shown that by iterative optimization of PNOs in coupled-cluster methods the PNO truncation error can be greatly reduced. 225 Similarly, PNOs can be computed purely numerically. 415 The…”
Section: Reduced-scaling CC Methods Based On Pair Natural Orbitalsmentioning
confidence: 99%
“…[222][223][224] Pilot implementation of pair natural orbital CC methods for ground-and excited-states have also been demonstrated. 223,225 7 Solvers…”
Section: Tiledarraymentioning
confidence: 99%
“…Due to their pioneering work, the LPNO and the DLPNO methods have been used successfully to study ground state properties of molecular systems previously unreachable by canonical correlated methods, such as a recent application to crambin containing 644 atoms . Recent work to improve the construction of ground‐state PNOs promises to expand the applicability of these methods even further …”
Section: Reduced Scaling: Localization Approachesmentioning
confidence: 99%